Large scale wind climatological examinations of wind energy utilization - Kircsi, Andrea (Acta Geographica Debrecina Landscape & Environment series, 2008)
The aim of this article is to describe the particular field of climatology which analyzes air movement characteristics regarding utilization of wind for energy generation. The article describes features of wind energy potential available in Hungary compared to wind conditions in other areas of the northern quarter sphere in order to assist the wind energy use development in Hungary. Information on wind climate gives a solid basis for financial and economic decisions of stakeholders in the field of wind energy utilization.